Histopathological tumor response following neoadjuvant hyperthermic isolated limb perfusion in extremity soft tissue sarcomas: Evaluation of the EORTC-STBSG response score. Issue 9 (September 2018) - Stevenson, Marc G.; Hoekstra, Harald J.; Song, Wangzhao; Suurmeijer, Albert J.H.; Been, Lukas B.
Abstract: Introduction: This study aims to evaluate the applicability and prognostic value of the European Organization for Research and Treatment of Cancer-Soft Tissue and Bone Sarcoma Group (EORTC-STBSG) histopathological response score in extremity soft tissue sarcoma (ESTS) patients treated with neoadjuvant hyperthermic isolated limb perfusion (HILP) and delayed surgical resection. Methods: Patients treated between 1991 and 2016 were included. The histopathological tumor response was established in accordance with the EORTC-STBSG response score. The distribution of patients was assorted according to the 5-tier histopathological response score for tumor grade, histological subtype and HILP regimen. Predictors for local recurrence free survival (LRFS) and overall survival (OS) were identified through Kaplan-Meier and Cox regression analyses. Results: Ninety-one patients were included and their resection specimens were reanalyzed. Which resulted in 11 Grade A (12.1%), ten Grade B (11.0%), 15 Grade C (16.5%), 22 Grade D (24.2%) and 33 Grade E (36.3%) responses found among the series. The histopathological response was significantly influenced by the HILP regimen used, p = 0.033. Median follow-up was 65.0 (18.0–157.0) months. The histopathological response was not associated with LRFS nor OS. Resection margins, HILP regimen and adjuvant radiotherapy were associated with LRFS. Patients' age, tumor grade, tumor size and histological subtype were predictors for OS. Conclusions: The EORTC-STBSG response score is applicable for determining the histopathological response to neoadjuvant ESTS treatment. However, this response does not seem to predict LRFS nor OS in locally advanced ESTS.